BUILDING VOCABULARY USING POP SONGS - Rahmatika Kayyis, author (JURNAL SMART, 2015)
The objective of the study is to find out whether there is a significant difference between the vocabulary mastery of first semester students taughtusing English pop songs and that taught without using English pop songs as a medium. This study involved 64 students of first semesterof STKIP Muhammadiyah Pringsewu Lampung in the academic year of 2012/2013 as the objects of the study. The result of the study shows there is a significant difference in the studentâs vocabulary mastery between the experimental group who are taughtusing English pop songs and that taught without using English pop songs as a medium.The mean of post test score of the experimental group is 16.93 while the mean score of the control group is 14.54. The result of t-test shows that t-observed value which is higher than the t-value of the table (2.572>1.99), with a probability value of 0.008 which is lower than the significance level (0.008 < 0.05). In conclusion, the use of English pop songscould improve the studentsâ vocabulary mastery.Keywords: Vocabulary, English Pop Songs